Strategi Pemasaran UMKM Mercon Sapi di Era Digital - Muza Paravel Adz Dzikri; Reinandez Farhan Defara Sinulingga; Olivia Ramadani; Golda Harry Briliant; Muhammad Jafar At-Tarmidzi; Santi Rimadias (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The rapid growth of digital technology has transformed the way Small and Medium Enterprises (SMEs), including beef mercon culinary businesses, promote their products and interact with customers. This community service activity aimed to assist the SME Warung Mercon Teh Sun in improving business promotion, expanding market reach, and enhancing service quality through the effective utilization of digital media. The activity employed participatory methods consisting of observation, interviews, discussions, program implementation, and evaluation of digital media utilization within the business. The implemented programs included the development of an Instagram account as a promotional platform, the creation of a mini website to provide product information and facilitate ordering services, and the design of a Google Form to collect customer satisfaction feedback. The results demonstrate that the application of digital media has helped the SME strengthen its online presence, increase promotional attractiveness, improve communication with customers, and support more effective marketing activities. Furthermore, customer satisfaction surveys generated valuable feedback that can be used by business owners to evaluate and improve product quality and service performance. The integration of digital marketing tools also contributes to increasing customer engagement and strengthening the competitiveness of the business in an increasingly digital marketplace. Therefore, the implementation of digital marketing strategies is expected to support sustainable business growth, improve customer satisfaction, and encourage SMEs to adapt more effectively to technological developments and changing consumer behavior. SMEs are expected to increase their competitiveness and achieve sustainable business growth.